2023
DOI: 10.35848/1882-0786/acc006
|View full text |Cite
|
Sign up to set email alerts
|

Axis thermal expansion switching in transition-metal zirconides TrZr2 by tuning the c/a ratio

Abstract: This study examines the temperature-dependent evolution of the lattice constants for various CuAl$_2$-type compounds, including NiZr$_2$, (Co,Rh,Ir)Zr$_2$, (Fe,Co,Rh,Ir)Zr$_2$, and (Co,Ni,Cu,Rh,Ir)Zr$_2$, in the pursuit of negative or zero thermal expansion. Results reveal that NiZr$_2$ has positive thermal expansion, while the other compounds exhibit uniaxial negative thermal expansion along the $c$-axis contraction. The study suggests that the $c$-axis thermal expansion can be controlled by manipulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…NiZr 2 exhibits PTE both along the a-and c-axes, and thus, the coefficient of volumetric thermal expansion 𝛽 is positive (Figure 1a). [19,20] In the tetragonal crystal structure, 𝛽 can be calculated according to the following equation:…”
Section: Thermal Expansion Under High Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…NiZr 2 exhibits PTE both along the a-and c-axes, and thus, the coefficient of volumetric thermal expansion 𝛽 is positive (Figure 1a). [19,20] In the tetragonal crystal structure, 𝛽 can be calculated according to the following equation:…”
Section: Thermal Expansion Under High Pressurementioning
confidence: 99%
“…[16][17][18] In the TrZr 2 system, we revealed that the uniaxial NTE along the c-axis can be controlled by the lattice constant ratio c/a, through chemical element substitution. [19,20] The sign of the linear coefficient of thermal expansion along the c-axis changes from positive to negative upon the substitution of Ni with Co at ambient pressure. [20] The anomalous bonding states related to the uniaxial NTE along the c-axis in TrZr 2 have also been observed using X-ray absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%